PENGARUH SUMBER DAYA MANUSIA, TEKANAN EKSTERNAL, KOMITMEN MANAJEMEN TERHADAP TRANSPARANSI PELAPORAN KEUANGAN - Purnamasari, Ratna Dewi Wulan; Handayani, Nur (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
This research examines the influence of human resources, external pressure, and management commitment to the implementation of the transparency of the financial reporting. The result of the analysis which has been done by the researcher shows that: 1) human resources does not have any significant influence to the implementation of the transparency of financial reporting, it indicates that the improvement of the quantity and quality of human resources is required by the organization in order to increase the transparency of financial reporting on the local government; 2) external pressure has significant influence to the implementation of the transparency of financial reporting, it means that when the external pressure is getting high, the transparency of the financial reporting will be better as well; 3) the management commitment does not have any significant influence to the implementation of the transparency of financial reporting. It shows that the management commitment cannot support the implementation of the transparency of the enhancement of financial reporting.Keywords: Human Resources, External Pressure, Management Commitment, Transparency of Financial Reporting